Contagion : sexuality, disease, and death in German idealism and romanticism - Krell, David Farrell (Studies in Continental thought., 1998)
"Although the Romantic Age is usually thought of as idealizing nature as the source of birth, life, and creativity, David Farrell Krell focuses on the preoccupation of three key German Romantic thinkers - Novalis, Schelling, and Hegel - with nature's destructive powers: contagion, disease, and death. Krell brings to light little-known texts by each writer that develop theories about the intertwined beneficent and maleficent aspects of nature. Krell's investigations reveal that the forces of sexuality and life are also seen as the carriers of disease and death. The insights of Novalis, Schelling, and Hegel offer surprisingly relevant perspectives for contemporary science and for our own thinking - in an age of contagion."--Jacket